Młodzi jako uczestnicy polskich przemian: beneficjenci czy przegrani? = Young people as participants in polish transformations: beneficiaries or losers? - Niezgoda, Marian (1943- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the last 120 years, Polish society has experienced very rapid social changes. It has survived two wars, the regaining of independence, post-partition reconstruction, WorldWar II and the collapse of communism. On top of that, there have been processes of change taking place on a global scale, revolutions in the sphere of politics (ideology), economy and culture, which have been accelerated and strengthened by scientific and technological revolutions. This raises the question: what impact did they have on the witnesses and participants in these transformations? How did they affect their fate? Obviously, they have been experienced by different generations, who had different life experiences or cultural experiences. They might have engaged in these processes differently. This article is concerned with the experiences of youth generations at moments of breakthroughs. This is what this text is devoted to. It is an essay, based on the publications of sociologists and the author?s experience. The focus was on asking questions rather than giving answers.
Keywords: pokolenie; zmiana społeczna; szansa; możliwości; nierówności; generations; social change; chance; opportunities; inequalities